Analisis Kinerja Keuangan Pada PT. Akra Corporindo Tbk. - Jamali, Hisnol (CV. Lafadz Jaya, 2023)
The purpose of the study is to see the development of the financial achievements of PT. AKRA Corporindo Tbk If the liquidation ratio, solvency ratio, profit ratio, activity ratio, and market valuation ratio. Investigators carry out investigations through investigators and review literature from libraries. The population in this study is all data on financial statements of PT Akra Corporindo Tbk, while the sample of this study is data from financial statements of PT. Akra Corporindo Tbk for 5 years from 2015 to 2019.If from the ratio of liquid, solvency, profit, activity and market valuation, it can be concluded briefly that the decision of PT. AKRA Corporindo Tbk from 2015 to 2019.PT. AKRA Corporindo Tbk A bad situation where the number and capital of the company increase every year if the net income, inventory, cash, and total assets owned by the company are more likely to fluctuate. So it may be reserved so that the company PT. AKRA Corporindo Tbk's financial management needs to be better so that the company continues to develop well every year and there is no savings in paying bonds or anything else.